Quantum chemistry research structure and electronic properties of peroxides - Grytselyak, Tymofiy; Shchodryi, Volodymyr; Dutka, Volodymyr; Kovalskyi, Yaroslav (Видавництво Львівської політехніки, 2013)
We have calculated the optimal structure, electronic properties and heat of formation (ΔfH ) peroxide compounds with the help of semiempirical quantum chemical methods. Theoretically calculated values well coincide with the values found from thermochemical experiments.
Keywords: Geometric structure; electronic properties; heat of formation; reactivity